2012
DOI: 10.1097/prs.0b013e318265f690
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Dermal Matrix in Irradiated Tissue Expander/Implant–Based Breast Reconstruction

Abstract: Use of acellular dermal matrix for implant-based breast reconstruction does not appear to increase or decrease the risk of complications, but it might provide psychological and aesthetic benefits. Multicenter or single-center randomized controlled trials that provide high-quality, level I evidence are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 40 publications
1
48
0
1
Order By: Relevance
“…Of the 40 comparative studies, the majority were retrospective (37), single‐centre (36) studies that reported the outcomes of two‐stage expander–implant reconstruction with and without ADM (25). Nine studies compared different types of ADM; three specifically evaluated the impact of radiotherapy on ADM‐assisted reconstruction, and five evaluated different aspects of the procedure including ADM size, antibiotic regimens, incision placement and single‐ versus two‐stage procedures. The median sample size was 63 (i.q.r.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 40 comparative studies, the majority were retrospective (37), single‐centre (36) studies that reported the outcomes of two‐stage expander–implant reconstruction with and without ADM (25). Nine studies compared different types of ADM; three specifically evaluated the impact of radiotherapy on ADM‐assisted reconstruction, and five evaluated different aspects of the procedure including ADM size, antibiotic regimens, incision placement and single‐ versus two‐stage procedures. The median sample size was 63 (i.q.r.…”
Section: Resultsmentioning
confidence: 99%
“…Animal studies and early clinical experience indicate a possible protective effect of acellular dermal matrix from capsular contracture. 29,30 The Breast Reconstruction Evaluation Using Acellular Dermal Matrix as a Sling Trial (BREASTrial) aims to prospectively compare AlloDerm versus DermaMatrix in immediate staged tissue expander breast reconstruction by analyzing complication rates, histologic characteristics, degree of matrix biointegration, tissue expander dynamics, and patient satisfaction with their breast reconstruction. The impact of obesity, postoperative radiation therapy, and chemotherapy on these outcomes will be closely evaluated.…”
mentioning
confidence: 99%
“…The literature reveals poor correlation between the onset of postoperative complications and the use of ADM [14,15]. A recent review by Clemens et al [16] proved a positive effect with the use of ADM in settings of irradiated breast tissue; it does not increase or decrease the risk of complications but instead provides psychological and aesthetic benefits.…”
Section: Discussionmentioning
confidence: 99%